Behavioural problems of adolescents in secure residential youth care: Gender differences and risk factors. Issue 2 (10th October 2022) - Gutterswijk, Raymond V.; Kuiper, Chris H. Z.; van der Horst, Frank C. P.; Jongerling, Joran; Harder, Annemiek T.; Prinzie, Peter
Abstract: Adolescents in secure residential care mostly suffer from serious behavioural problems, often accompanied by trauma and adverse family circumstances. This paper presents findings of a comparison of behavioural problems and risk factors of 255 boys and girls (aged 12 to 18 years) in secure residential care in the Netherlands and their association with behavioural problems. A cross‐sectional design and standardized questionnaires were used to measure behavioural problems and individual and familial risk factors. By using independent‐sample t tests, the severity of these factors in boys and girls was compared, and by using structural equation modelling (SEM), associations between these factors and behavioural problems were investigated. The findings of the study show that post‐traumatic stress disorder (PTSD) symptoms, maladaptive emotion regulation, impaired perceived competence and internalizing behavioural problems were more severe in girls than in boys. Boys experienced more severe externalizing behavioural problems and more family problems than girls. Maladaptive emotion regulation, PTSD symptoms, perceived competence and parenting problems were related to behavioural problems. The results indicate that treatment for girls should address PTSD symptoms, perceived competence and maladaptive emotion regulation and that extra attention for family problems in the treatment of boys is warranted.